Difference in allostatic interoceptive network connectivity by cognitive status. (31st December 2021) - Bateman, James R.; Kawas, Mohammad I; Craft, Suzanne; Lockhart, Samuel N.; Kim, Jeongchul; Sai, Kiran K Solingapuram; Lindquist, Kristen A; Whitlow, Christopher T.
Abstract: Background: The allostatic interoceptive network (AIN) has been proposed as central to linking interoceptive processing and autonomic regulation and involved in emotional experience. Early pathologic changes in AD occur in hubs of the AIN, and changes in emotional reactivity have been identified at both the MCI and dementia stages of Alzheimer's disease. Interoception has been proposed as a core feature in psychiatric disease, though relatively little attention has been paid to altered interoception in neuropsychiatric symptoms in dementia. We conducted a pilot analysis in cognitively normal (CN) participants and those with mild cognitive impairment (MCI) to identify alterations in functional connectivity of the AIN, default mode, and salience networks. Method: Twenty‐two participants from the Wake Forest Alzheimer's Disease Research Center (ADRC) Clinical Core cohort including CN participants (n = 11, mean age = 67 ± 7) and MCI (n = 11, mean age = 72 ± 7) received 3T brain MRI using T1 for gray/white matter segmentation and BOLD for resting‐state functional connectivity. BOLD time series data were pre‐processed and de‐noised using standard techniques. Connectivity analyses were performed using the CONN functional connectivity toolbox. Briefly, we performed a comparison of within‐network connectivity of the allostasis and interoception system (comprised of the DMN, SN, and AIN seed regions) between MCI and NC participants while adjusting for age (p < 0.05 uncorrected). Result: Table lists the baseline demographic and clinical characteristics for CN and MCI groups. Participants with MCI had greater connectivity between limbic regions of the AIN and salience network compared with the CN group, and decreased connectivity between the left lateral parietal cortex and multiple hubs of the salience network. Within the AIN seed regions, the amygdala and dorsal posterior and mid insula had increased connectivity (Figure ; p < 0.05 uncorrected). Conclusion: We find differences in functional connectivity between CN adults and persons with MCI for three brain networks. Our analyses provide preliminary support that changes in an integrated allostasis and interoceptive system, integrating components of the DMN and SN, may have implications for emotional dysregulation in ADRD.